The role of semantic abstractness and perceptual category in processing speech accompanied by gestures - Nagels, Arne; Chatterjee, Anjan; Kircher, TIlo; Straube, Benjamin (Frontiers in Behavioral Neuroscience, 2013)
Space and shape are distinct perceptual categories. In language, perceptual information can also be used to describe abstract semantic concepts like a ‘rising income’ (space) or a ‘square personality’ (shape). Despite being inherently concrete, co-speech gestures depicting space and shape can accompany concrete or abstract utterances. Here, we investigated the way that abstractness influences the neural processing of the perceptual categories of space and shape in gestures. Thus, we tested the hypothesis that the neural processing of perceptual categories is highly dependent on language context. In a two-factorial design, we investigated the neural basis for the processing of gestures containing shape (SH) and spatial information (SP) when accompanying concrete (c) or abstract (a) verbal utterances. During fMRI data acquisition participants were presented with short video clips of the four conditions (cSP, aSP, cSH, aSH) while performing an independent control task. Abstract (a) as opposed to concrete (c) utterances activated temporal lobes bilaterally and the left inferior frontal gyrus (IFG) for both shape-related (SH) and space-related (SP) utterances. An interaction of perceptual category and semantic abstractness in a more anterior part of the left IFG and inferior part of the posterior temporal lobe indicates that abstractness strongly influenced the neural processing of space and shape information. Despite the concrete visual input of co-speech gestures in all conditions, space and shape information is processed differently depending on the semantic abstractness of its linguistic context.